Forms of Violence and Legal Protection of Women in Cases of Arrest in Southwest Sumba District - Patrick Sebastian Ndara Tanggu Holo (Jurnal Restorasi : Hukum dan Politik, 2023)
Arrest marriage (Paneta mawinne) in Southwest Sumba Regency still exists and is carried out continuously with forced marriages on women which results in victims experiencing acts of violence. That the tradition of marrying under arrest still has a patriarchal culture with high customs, however, when viewed from the perspective of positive law, it can be considered as an act of kidnapping. The formulation of the main problems of this research are: (1) What are the forms of violence against women in the case of intermarriage in Mareda Kalada Village, East Wewewa District, Southwest Sumba Regency. (2) What is the legal protection for women who are victims of violence in the case of intermarriage in Mareda Kalada Village, East Wewewa District, Southwest Sumba Regency. This research is an empirical juridical research where this research was carried out at the East Wewewa Sub-district Office and the Office of the Mareda Kalada Wewewa Timur Village Head. This study used interview guidelines with seven informants. The data are presented in simple tables and analyzed in a qualitative descriptive manner. Based on the results of the research that has been done, it can be concluded: (1) Forms of Violence in Arresting Marriages against Women are physical violence and psychological violence. (2) Legal protection given to victims of marital violence against women in Mareda Kalada Village, East Wewewa District, Southwest Sumba Regency is preventive legal protection, repressive legal protection and customary law protection